GRAZING ACTIVITY OF THE SEA URCHIN TRIPNEUSTES GRATILLA IN TROPICAL SEAGRASS BEDS OF BUTON ISLAND, SOUTHEAST SULAWESI, INDONESIA - Ma'ruf Kasim (JOURNAL OF COASTAL DEVELOPMENT, 2009)
The research on grazing activity of a sea urchin (Tripneustes gratilla) in tropical seagrass beds wasconducted in Buton Island. The objectives of the research were to study the grazing activity such as foodpreference, grazing rate and grazing times of T. gratilla in tropical seagrass community. The results of theresearch showed that Thalassia hemprichii and Enhalus acoroides are primary food items of T. gratilla andcontained on average of 55 % and 31 % of the gut contents, respectively. The grazing rate of an individualranged from 9.6 - 14.1 g wet weight in 24 hours. The grazing times of T. gratilla were between 01.00 - 11.00a.m. and 15.00 - 21.00 p.m.